Gender Dimensions of Community-Driven Development Operations : A Toolkit for Practitioners - World Bank (World Bank, Washington, DC, 2017)
Community-development development (CDD) programs require monitoring and evaluation (M&E) to tell those implementing and funding the programs whether they are on track to deliver, or have delivered, desired outcomes such as improved services, economic activity, and empowerment. The objective of this toolkit is to provide practical guidance to World Bank EAP operational task teams and other CDD practitioners (i.e. government/non-government organization (NGO) staff) on how to measure the gendered impact of CDD operations. First, this is necessary because CDD program reviews have found that gender indicators are not widely used. Second, several governments in the East Asia and Pacific (EAP) region have identified gender as an important pillar in poverty alleviation strategies, in the light of evidence suggesting that societies promoting more equal opportunities for men and women have higher growth, lower poverty, and better development outcomes. Third, gender mainstreaming is a critical facet of World Bank policy and programs. Fourth, as this toolkit demonstrates, it is straightforward to add gender indicators to a results framework. It involves disaggregating some of the indicators that will already be in the results framework by gender, as well as adding a limited number of specific gender indicators. This toolkit takes CDD practitioners and other interested readers through the necessary steps to identify where to track gender in the results framework, as well as suggesting possible indicators. This toolkit is organized in three sections: section one set out why gender matters for CDD mentoring and evaluation (M&E); section two provides an introduction (and pointers to further reading) on M&E topics that the non-specialist will find useful when constructing gender indicators. This includes a generic CDD results framework structure that provides convenient categories for incorporating gender M&E indicators; section three uses these categories to provide examples of indicators (and other evidence) from the EAP region and illustrates how gender M&E can be added to CDD program results frameworks.